Zinc and Macular Degeneration. (8th October 2014) - Unknown
Abstract : A zinc metalloenzyme of the lysosomal apparatus of the retinal pigment epithelium of humans has been shown to lose activity with age. Zinc supplements may retard the rate of loss of visual acuity in subjects with age-related macular degeneration.